THE EPIDEMIOLOGY OF EMERGING AND RE-EMERGING INFECTIOUS DISEASES - Abdullah Rashid Alharbi,‏ Saud Mohammed Abdulrahman Alqarni, ‏Jalal Ahmed Sabi,‏ Ali Zyiad Almutairi,‏ Saad Refaei Mawtan Alotaibi,‏ Mohammed Saleh Mobarak Al-Harqan,‏; Ramzi Ahmed Darraj,‏ Yahia Mohammed Sahli, ‏Ali Abdu Arishi,‏ Mohammed Hassan Sahli,‏ Mohammed Sultan Hakami, ‏Mohammed Ali Sahli,‏ Mansour Mohammed Sumayli,‏; Rashid Mohammed Amer Al Dosari, Fawaz Dakhel Fahad Bin Jadeed, Yahia Hadi Hadi Najjar (Chelonian Research Foundation, 2022)
Globally, vector-borne illnesses that are emerging or reemerging provide a serious threat to public health. In the last 20 years, several of these illnesses have spread to new areas and are resurfacing or forming at an accelerating rate. Research has shown that the emergence or reemergence of these diseases is largely determined by the interactions that occur between pathogens, hosts, and the environment. Furthermore, the introduction and/or reemergence of vector-borne diseases has been strongly connected to socioeconomic and demographic factors as travel, trade, urbanization, globalization, human population growth, and intimate relationships with livestock. Other studies highlight the main aggravating factors for the establishment and reemergence of vector-borne infectious diseases as the continuous evolution of infections, the growth of reservoir populations, and the usage of antibiotic drugs. Certain research, however, categorically assert that vector-borne infectious disease emergence and comeback are related to climate change. Our ability to prevent the numerous newly developing and resurgent vector-borne infectious diseases that may occur in the future appears doubtful, even if many significant emerging and re-emerging vector-borne infectious diseases are becoming better controlled. In order to investigate global trends of developing and re-emerging vector-borne illnesses as well as the difficulties in controlling them, this work evaluates and synthesizes the body of existing information. Additionally, it makes an effort to shed light on the epidemiological characteristics of the main vector-borne illnesses, such as dengue, Chikungunya, West Nile fever, Chikaungunya fever, Rift Valley fever, Zika fever, and Crimean-Congo hemorrhagic fever. Keywords: Vector-borne disease, emerging, re-emerging disease, global trends, review.